Preparation method and application of nano-carbon suspension injection

By using poloxamer as a suspension agent during the preparation of nanocharcoal suspension injection and performing pretreatment of nanocharcoal, the problems of increased consistency and impaired coagulation function caused by dispersing suspended auxiliary materials in the prior art are solved, and higher purity, stability and lymphatic tracing speed are achieved.

CN112168775BActive Publication Date: 2025-04-29SICHUAN ENRAY PHARM TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202011061799.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-09-30
Publication Date
2025-04-29
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

The dispersed suspension auxiliary materials used in the preparation of existing nanocharcoal suspension injections lead to an increase in the consistency of the suspension, affecting the lymphatic tracing speed, and polyvinylpyrrolidone may affect blood coagulation function.

Method used

Poloxamer is used as a suspension agent to improve the purity of nanocharcoal by pretreatment methods such as ethyl acetate degreasing, acid washing, and alkali washing, and nanocharcoal suspension is formed under the mechanical action of high shear grinding and dispersion equipment. This method avoids the use of polyvinylpyrrolidone, reduces the complexity of the preparation process, and improves the stability of the product.

Benefits of technology

It improves the purity and stability of nanocharcoal suspension injection, increases the speed of lymphatic tracer, avoids impaired blood clotting function, reduces preparation costs, and extends shelf life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002712590210000051
    Figure BDA0002712590210000051
  • Figure BDA0002712590210000061
    Figure BDA0002712590210000061
  • Figure BDA0002712590210000091
    Figure BDA0002712590210000091
Patent Text Reader

Abstract

The invention provides a nano-carbon suspension injection. Every 1000 mL of the nano-carbon suspension injection comprises: 20-100 g of nano-carbon, 17-30 g of a suspending agent, 2-4 g of a pH regulator, 8-10 g of sodium chloride, and the remainder is water for injection. The invention also specifically discloses a preparation method thereof. The invention adopts poloxamer as a suspending agent, thereby overcoming the defects of the suspending agent in the prior art having a hemolytic risk, the complex process of the prior method, and the poor product stability. The invention further standardizes the use of nano-carbon raw materials and the pretreatment steps, thereby obtaining a nano-carbon injection with low heat source and good stability, and is conducive to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of medical tracer diagnostic reagents, and specifically relates to a preparation method and application of a nano-carbon suspension injection. Background Art

[0002] Lymph node metastasis is an important cause of postoperative recurrence of solid cancer, especially cervical cancer, thyroid cancer, gastric cancer and other cancers. Therefore, thorough lymph node dissection is particularly important and helps to prolong postoperative survival. Even in the early stages of solid cancer, 10% to 25% of patients have local lymph node metastasis. However, lymph nodes are usually hidden in adipose tissue and accompany large blood vessels. It is often very difficult to completely remove these draining lymph nodes in the blood-stained surgical field. Moreover, the lymphatic drainage of the upper and lower parts of the organs is also different. Therefore, the scope of lymph node dissection is related to the location of the cancer. If unnecessary lymph nodes are included in order to completely remove the lymph nodes, the surgical trauma is too large and the quality of life of the patient after surgery is significantly reduced. Therefore, if living lymph node staining can be used during surgery to help doctors completely remove lymph nodes, it is the key to improving the treatment effect of malignant tumors. Tracers are often used clinically to track metastatic lesions. The third generation of tracers, represented by nanocarbon suspension, is the most effective tracer currently. It can enter the lymphatic system and be engulfed by macrophages and then accumulate in the lymph nodes, making the lymph nodes appear black. Related studies have shown that the smaller the tumor, the higher the feasibility and safety of nanocarbon suspension injection in tracing sentinel lymph nodes.

[0003] At present, there are many successful clinical experiences, such as Zhang Ya [1] et al. found that nanocarbon suspension injection can effectively trace the sentinel lymph nodes of patients with cervical cancer, and it has no significant effect on the patient's operation time, intraoperative blood loss, lymph node dissection and postoperative pathological results. It is a safe and efficient sentinel lymph node tracer for cervical cancer; Lou Chaosheng [2] et al. found that in the surgical treatment of 86 patients with thyroid cancer, a total of 487 lymph nodes were detected in the observation group, of which 458 were black-stained and 29 were not black-stained, with an average of (10.5±3.7) nodes / case; a total of 288 lymph nodes were detected in the control group, with an average of (6.1±2.8) nodes / case; the difference in the average number of detections between the two groups was statistically significant (t=6.218, P<0.05). There were 208 lymph nodes with cancer cell metastasis in the observation group, with an average of (4.2±1.6) nodes / case; there were 112 lymph nodes with cancer cell metastasis in the control group, with an average of (2.2±0.9) nodes / case; the difference in the average number of lymph nodes cleared with cancer cell metastasis between the two groups was statistically significant (t=7.144, P<0.05). No parathyroid missection was found in the observation group, while 5 cases of missection and hypocalcemia occurred in the control group. The number of cases of parathyroid missection in the observation group was significantly lower than that in the control group, and the difference was statistically significant (χ2 =5.309, P<0.05). Intraoperative injection of nanocarbon suspension can increase the number of lymph nodes detected and effectively avoid mis-resection of parathyroid glands.

[0004] The nanocarbon in the nanocarbon suspension injection is an ultrafine carbon particle with a particle size in the nanometer range, and the lymphatic system has the characteristic of engulfing tiny foreign bodies. After the nanocarbon suspension injection is injected into the local tissue, the macrophages quickly engulf these ultrafine carbon particles and enter the drainage lymphatic vessels and lymph nodes, so that a large number of ultrafine carbon particles are retained and dyed black, thereby realizing the in vivo staining of the lymph nodes in the tumor area and playing the role of lymphatic tracing. In addition, nanocarbon has a strong adsorption capacity and can reversibly adsorb chemotherapy drugs such as methotrexate, mitomycin and pingyangmycin, so it has the potential to be used as a directional carrier for lymphatic chemotherapy. Chinese invention patent CN1181134C "A method for preparing a nanocarbon suspension composition" discloses a method for preparing a nanocarbon suspension for tracing regional drainage lymph nodes of malignant tumors. The characteristics of its technical solution are: because the surface structure of nanocarbon is hydrophobic, it cannot be directly dispersed in an aqueous solution to form a nanocarbon suspension, so it is necessary to add a dispersing and suspending auxiliary material, and the nanocarbon suspension can be formed under the mechanical action of a high shear force grinding and dispersing device. After the nanocarbon suspension is injected into the local tissue, it can selectively enter the drainage lymph nodes of the local tissue, dye these lymph nodes black, help doctors identify the lymph nodes with the naked eye, achieve the effect of lymphatic tracing, and thus facilitate the clearance of these lymph nodes. However, the dispersing and suspending excipients in it cause the suspension to become thicker, which hinders further improving the lymphatic tracing speed. Moreover, according to the information of the US FDA, if polyvinyl pyrrolidone, which is used as a dispersing and suspending excipient, enters the blood, it may affect the coagulation function. Summary of the invention

[0005] In order to overcome the defects of the prior art, the present invention adopts the following technical solutions:

[0006] On one hand, the present invention provides a nano-carbon suspension injection, wherein each 1000 mL of the nano-carbon suspension injection comprises: 20-100 g of nano-carbon, 17-30 g of a suspending agent, 2-4 g of a pH regulator, 8-10 g of sodium chloride, and the remainder is water for injection;

[0007] Furthermore, the nanocarbon suspension injection comprises: 50 g of nanocarbon, 20 g of suspending agent, 3 g of pH regulator, 9 g of sodium chloride, and the balance is water for injection;

[0008] Further, the nanocarbon is any one of nanocarbon particles and graphene; preferably, the nanocarbon is nanocarbon particles; further preferably, the nanocarbon is carbon black;

[0009] Further preferably, the particle size of the nanocarbon is 100nm to 220nm; preferably, the particle size of the nanocarbon is 160 to 180nm;

[0010] Further, the suspending agent is any one of poloxamer, polyvinyl pyrrolidone C30 (PVP C30), and Tween-80; preferably, the suspending agent is poloxamer; more preferably, poloxamer 188;

[0011] Further, the pH adjuster is any one of sodium citrate, sodium acetate, sodium borate, sodium phosphate, and sodium bicarbonate; preferably, the pH adjuster is sodium citrate;

[0012] The second aspect of the present invention provides a method for preparing any one of the above-mentioned nano-carbon suspension injections, comprising the following steps:

[0013] S1 Pretreatment of nanocarbon: After the nanocarbon is degreased with ethyl acetate, it is first washed with acid, then washed with water until the nanocarbon is nearly neutral, then washed with alkali, and then washed with water until the nanocarbon is nearly neutral, that is, the nanocarbon is obtained;

[0014] S2: Weigh the raw materials and excipients according to the above formula, then take 90% v / v of the above formula amount of water for injection, add the weighed sodium chloride and stir until it is completely dissolved to obtain a saline solution;

[0015] S3: adding the weighed sodium citrate and poloxamer to the saline solution obtained in S2 and stirring until they are completely dissolved to obtain an auxiliary material solution;

[0016] S4: adding the weighed nano-carbon to the auxiliary material liquid obtained in S3 and stirring evenly, and then adding the remaining amount of water for injection to obtain a fixed volume solution;

[0017] S5: Then the fixed volume solution obtained in S4 is homogenized at a speed of 15000-20000 rpm for 3-10 minutes, and then homogenized at a pressure of 15000-30000 psi for 1-5 times, and then filled and capped, and then steam sterilized at 115-130° C. for 10-30 minutes to obtain;

[0018] Further, the mass of nanocarbon in step S1: volume of ethyl acetate is 1 g: 5-12 / ml;

[0019] Further, the acid in step S1 is HNO3; further, the base in step S1 is NaOH;

[0020] Furthermore, the HNO3 is an 8-15% v / v HNO3 aqueous solution, preferably, the HNO3 is a 10% v / v HNO3 aqueous solution; further, the NaOH is a 0.08-0.15 mol / L NaOH aqueous solution; the NaOH is a 0.10 mol / L NaOH aqueous solution;

[0021] Furthermore, the mass of nanocarbon in step S1: acid volume is 1g:3-5 / ml, preferably, the mass of nanocarbon in step S1: acid volume is 1g:4 / ml;

[0022] Furthermore, the mass of nanocarbon in step S1: the volume of alkali is 1g:3-5 / ml; preferably, the mass of nanocarbon in step S1: the volume of alkali is 1g:4 / ml;

[0023] Furthermore, the homogenization speed described in S5 is 18000 rpm, and the homogenization time is 5 min;

[0024] Furthermore, the homogenization pressure in S5 is 20000 psi, and the number of homogenizations is 3 times;

[0025] Furthermore, the sterilization temperature described in S5 is 121° C. and the sterilization time is 15 min.

[0026] Beneficial Effects

[0027] 1. Since carbon black is a chemical product, the ash and heavy metals contained in it are somewhat different from the requirements of injection raw materials, and nano-carbon has trace amounts of fat-soluble substances remaining due to the influence of production raw materials and production methods. Therefore, in order to meet the requirements for medicinal use, the present invention adopts a series of pre-treatment methods to improve the purity of nano-carbon so that it meets the requirements of injection raw materials;

[0028] 2. The present invention adopts poloxamer as a suspending agent, thereby avoiding the hemolysis phenomenon caused by polyvinyl pyrrolidone entering the blood, overcoming the need to use a vibration mill to disperse raw and auxiliary materials in the prior art, and the final product particle size is stable after being prepared into an injection solution, and the shelf life is extended; and the current conventional wet heat sterilization process can be adopted, and the particle size and stability are not affected after sterilization, that is, the complexity of the preparation process is greatly reduced and the cost is reduced, which is conducive to industrial production. DETAILED DESCRIPTION

[0029] In a specific embodiment, the nano carbon particles used in the present invention are fine chemical products No. 40 carbon black, No. MA100 carbon black or No. MA77 carbon black produced by Mitsubishi Chemical Corporation of Japan;

[0030] In a specific embodiment, the poloxamer used in the present invention is poloxamer 188.

[0031] In a specific embodiment, in the method for preparing the nanocarbon suspension injection adopted by the present invention, the pretreatment of the S1 nanocarbon specifically includes:

[0032] S11: Degreasing was performed four times by adding ethyl acetate in the following order: nanocarbon mass: ethyl acetate volume 1g:5mL, 1g:1mL, 1g:4mL and 1g:1mL, and the crude nanocarbon was obtained after drying;

[0033] S12: Wash once with 10% v / v HNO3 aqueous solution in the ratio of 1 g of crude nanocarbon to 10% v / v HNO3 aqueous solution in the ratio of 4 mL, and then continue to rinse six times with water in the ratio of 1:4 of crude nanocarbon to purified water to obtain acid-washed nanocarbon;

[0034] S13: adding 0.1 mol / L NaOH aqueous solution to wash once with the mass of the crude nanocarbon: the volume of 0.1 mol / L NaOH aqueous solution of 1 g: 4 mL, and then continue to add water to rinse 6 times with the mass of the crude nanocarbon: the volume of purified water of 1 g: 4 mL to obtain alkali-washed nanocarbon, which is then dried;

[0035] Examples 1 to 7

[0036] 1.1 Composition of Examples 1 to 7 (per 1000 mL of nanocarbon suspension injection)

[0037]

[0038]

[0039] Embodiment 1: The preparation method comprises the following steps:

[0040] S1 Pretreatment of nanocarbon: S11: Add 90.0g No. 40 carbon black, 450mL ethyl acetate and a large magnet to a 500mL reaction bottle, stir and heat in a water bath until ethyl acetate refluxes, keep warm and stir for 1 hour, and filter while hot; wash the filter cake with 90mL of room temperature ethyl acetate, and filter to obtain a filter cake; transfer the filter cake to a 500mL reaction bottle again, add 360mL ethyl acetate and a large magnet, stir and heat in a water bath until ethyl acetate refluxes, keep warm and stir in a water bath for 1 hour, and filter while hot; wash the filter cake with 90mL of room temperature ethyl acetate, and filter to obtain a filter cake; vacuum dry the filter cake at 85°C for 2 hours to obtain 88.6g of crude carbon black; S12: Weigh 73.0g of crude carbon black, add Add 300mL of 10% v / v nitric acid aqueous solution and a magnetic particle, stir and slurry for 2 hours at room temperature, and filter with 300mL of purified water at room temperature for 6 times, and finally filter and stop washing when the pH of the filtrate is 6-7 to obtain acid-washed carbon black; S13: transfer the acid-washed carbon black to a beaker, add 300mL of 0.1mol / L sodium hydroxide and a magnetic particle, stir and slurry for 1 hour at room temperature, and filter with 300mL of ultrapure water at room temperature for 6 times, and finally stop washing when the pH of the filtrate is about 7 to obtain alkali-washed carbon black, and air dry the alkali-washed carbon black at 120°C for 5 hours to obtain 71.8g of solid. Yield: 98.4%.

[0041] S2: Weigh the raw materials and excipients according to the above formula, then take 90% v / v of the above formula amount of water for injection, add sodium chloride and stir until completely dissolved to obtain a saline solution;

[0042] S3: adding the weighed sodium citrate and poloxamer to the saline solution obtained in S2 and stirring until they are completely dissolved to obtain an auxiliary material solution;

[0043] S4: adding the weighed nano-carbon to the auxiliary material liquid obtained in S3 and stirring evenly, and then adding the remaining amount of water for injection to obtain a fixed volume solution;

[0044] S5: The fixed volume solution obtained in S4 is homogenized at a rotation speed of 15000 rpm for 10 minutes, and then homogenized once at a pressure of 15000 psi, and then filled and capped, and then steam sterilized at 115°C for 30 minutes.

[0045] Embodiment 2: The preparation method comprises the following steps:

[0046] S1 Pretreatment of nanocarbon: S11: Add 90.0 g of No. 40 carbon black, 450mL ethyl acetate and a large magnetic particle, stir and heat in a water bath until ethyl acetate refluxes, keep warm and stir for 1 hour, and filter while hot; wash the filter cake with 90mL of room temperature ethyl acetate, and filter to obtain a filter cake; transfer the filter cake to a 500mL reaction bottle again, add 360mL ethyl acetate and a large magnetic particle, stir and heat in a water bath until ethyl acetate refluxes, keep warm and stir in a water bath for 1 hour, and filter while hot; wash the filter cake with 90mL of room temperature ethyl acetate, and filter to obtain a filter cake; vacuum dry the filter cake at 85°C for 2 hours to obtain 88.6g of crude carbon black; S12: weigh 73.0g of crude carbon black, add 300mL of 10% v / v nitric acid aqueous solution and a magnetic particle, stir and beat for 2 hours at room temperature and filter, stir and beat the filter cake with 300mL of purified water at room temperature for 6 times, and finally stop washing after the filtrate has a pH of 6 to 7 to obtain acid-washed carbon black; S13: transfer the acid-washed carbon black into a beaker, add 300mL 0.1 mol / L sodium hydroxide and magnetic particle, stir and slurry for 1 hour at room temperature, filter, stir and slurry the filter cake with 300 mL ultrapure water at room temperature for 6 times, and stop washing when the pH of the filtrate is about 7 to obtain alkali-washed carbon black, and air-dry the alkali-washed carbon black at 120°C for 5 hours to obtain 71.8 g of solid. Yield: 98.4%.

[0047] S2: Weigh the raw materials and excipients according to the above formula, then take 90% v / v of the above formula amount of water for injection, add sodium chloride and stir until completely dissolved to obtain a saline solution;

[0048] S3: adding the weighed sodium citrate and poloxamer to the saline solution obtained in S2 and stirring until they are completely dissolved to obtain an auxiliary material solution;

[0049] S4: adding the weighed nano-carbon to the auxiliary material liquid obtained in S3 and stirring evenly, and then adding the remaining amount of water for injection to obtain a fixed volume solution;

[0050] S5: Then the fixed volume solution obtained in S4 is homogenized at a speed of 20,000 rpm for 3 minutes, and then homogenized once at a pressure of 30,000 psi, and then filled and capped, and then steam sterilized at 130° C. for 10 minutes to obtain;

[0051] Example 3: Its preparation method is the same as that of Example 1.

[0052] Embodiment 4: Its preparation method is the same as that of embodiment 2.

[0053] Embodiment 5: Its preparation method comprises the following steps:

[0054] S1 Pretreatment of nanocarbon: S11: Add 90.0g No. 40 carbon black, 450mL ethyl acetate and a large magnet to a 500mL reaction bottle, stir and heat in a water bath until ethyl acetate refluxes, keep warm and stir for 1 hour, and filter while hot; wash the filter cake with 90mL of room temperature ethyl acetate, and filter to obtain a filter cake; transfer the filter cake to a 500mL reaction bottle again, add 360mL ethyl acetate and a large magnet, stir and heat in a water bath until ethyl acetate refluxes, keep warm and stir in a water bath for 1 hour, and filter while hot; wash the filter cake with 90mL of room temperature ethyl acetate, and filter to obtain a filter cake; vacuum dry the filter cake at 85°C for 2 hours to obtain 88.6g of crude carbon black; S12: Weigh 73.0g of crude carbon black, add Add 300mL of 10% v / v nitric acid aqueous solution and a magnetic particle, stir and slurry for 2 hours at room temperature, and filter with 300mL of purified water at room temperature for 6 times. Finally, stop washing after the pH of the filtrate is 6-7 to obtain acid-washed carbon black; S13: Transfer the acid-washed carbon black to a beaker, add 300mL of 0.1mol / L sodium hydroxide and a magnetic particle, stir and slurry for 1 hour at room temperature, and filter with 300mL of ultrapure water at room temperature for 6 times. Finally, stop washing after the pH of the filtrate is about 7 to obtain alkali-washed carbon black. The alkali-washed carbon black is air-dried at 120°C for 5 hours to obtain 71.8g of solid. Yield: 98.4%;

[0055] S2: Weigh the raw materials and excipients according to the above formula, then take 90% v / v of the above formula amount of water for injection, add sodium chloride and stir until completely dissolved to obtain a saline solution;

[0056] S3: adding the weighed sodium citrate and poloxamer to the saline solution obtained in S2 and stirring until they are completely dissolved to obtain an auxiliary material solution;

[0057] S4: adding the weighed nano-carbon to the auxiliary material liquid obtained in S3 and stirring evenly, and then adding the remaining amount of water for injection to obtain a fixed volume solution;

[0058] S5: The fixed volume solution obtained in S4 is homogenized at a rotation speed of 18000 rpm for 5 minutes, and then homogenized at a pressure of 20000 psi for 3 times, and then filled and capped, and then steam sterilized at 121° C. for 15 minutes.

[0059] Example 6: Its preparation method is the same as that of Example 5.

[0060] Example 7: Its preparation method is the same as that of Example 5.

[0061] 8. Experimental example - prescription screening

[0062] Note: In the following experiments, "w" means unsterilized, "m" means sterilized, and "NA" means not measured.

[0063] 8.1 Screening of suspending agents

[0064] 8.1.1 Prescription and preparation process: On the basis of keeping the other components and dosages of the prescription and the preparation process unchanged, the types of suspending agents in the prescription are screened, and the prescription design is shown in Table 1 below. Prescription design (Specification: 50 mg / ml, Batch: 50 vials)

[0065] Table 1

[0066]

[0067] The preparation process of comparative examples 1 to 6 includes: S1 pretreatment of nanocarbon: S11: 90.0g No. 40 carbon black, 450mL ethyl acetate and a large magnetic particle are added to a 500mL reaction bottle, heated in a water bath with stirring until ethyl acetate refluxes, kept warm and stirred for 1 hour, and filtered while hot; the filter cake is washed with 90mL of ethyl acetate at room temperature, and filtered to obtain a filter cake; the filter cake is transferred to a 500mL reaction bottle again, 360mL ethyl acetate and a large magnetic particle are added, heated in a water bath with stirring until ethyl acetate refluxes, kept warm and stirred in a water bath for 1 hour, and filtered while hot; The filter cake was washed with 90 mL of ethyl acetate at room temperature and filtered to obtain a filter cake; the filter cake was vacuum dried at 85°C for 2 hours to obtain 88.6 g of crude carbon black; S12: 73.0 g of crude carbon black was weighed, 300 mL of 10% v / v nitric acid aqueous solution and a magnetic particle were added, the mixture was stirred and slurried at room temperature for 2 hours, and the filter cake was stirred and slurried with 300 mL of purified water at room temperature for 6 times, and the filtrate was filtered to a pH of 6 to 7 and then washing was stopped to obtain acid-washed carbon black; S13: the acid-washed carbon black was transferred to a beaker, 300 mL of 0.1 mol / L hydrogen was added, and the mixture was stirred and slurried for 2 hours at room temperature. Sodium oxide and magnetic particles were stirred and slurried for 1 hour at room temperature and filtered. The filter cake was stirred and slurried with 300 mL of ultrapure water at room temperature for 6 times. The pH of the filtrate was about 7 and then washing was stopped to obtain alkali-washed carbon black. The alkali-washed carbon black was dried by blast drying at 120° C. for 5 hours to obtain 71.8 g of solid; S2: The raw and auxiliary materials were weighed according to the above formula, and then 90% of the above formula amount of water for injection was taken, and sodium chloride was added and stirred until completely dissolved to obtain a salt solution; S3: The weighed sodium citrate and povidone C30 (Comparative Example 2) were added to the salt solution obtained in S2. S4: adding the weighed nanocarbon to the excipient solution obtained in S3 and stirring evenly, and then adding the remaining amount of water for injection to obtain a fixed volume solution; S5: then homogenizing the fixed volume solution obtained in S4 at a speed of 18000 rpm for 5 minutes, and then homogenizing at a pressure of 20000 psi for 3 times, and then filling, rolling and capping, and then steam sterilizing at 121°C for 15 minutes to obtain the product.

[0068] 8.1.2 pH value and particle size test results are shown in Table 2

[0069] Table 2

[0070]

[0071]

[0072] 8.1.3 Experimental Conclusion

[0073] From the above test results, the particle sizes of povidone C30, Tween 80 and polyoxyethylene (35) castor oil before sterilization were all less than 200nm, but exceeded the limit after sterilization. The particle sizes of sodium deoxycholate before and after sterilization were less than 200nm, but their pH values ​​exceeded the range of 6-8. The others did not meet the requirements, so poloxamer was selected as the suspending agent.

[0074] 8.2. Screening of main drugs

[0075] 8.2.1 Prescription and preparation process: On the basis of keeping the other components and dosage of the prescription and the preparation process unchanged, the types of main drugs in the prescription are evaluated and screened, and the prescription design is shown in Table 3 below. Prescription design (Specification: 50 mg / ml, Batch: 50 vials)

[0076] Table 3

[0077]

[0078] 8.2.2 pH value and particle size test results are shown in Table 4

[0079] Table 4

[0080]

[0081]

[0082] 8.2.3 Experimental Conclusion

[0083] From the above test results, it can be seen that the three types of carbon black selected in Examples 5 to 7 can all obtain pH and particle size that meet the requirements.

[0084] 8.3 Screening of auxiliary material dosage

[0085] On the basis of the basic prescription, keep the prescription type, model and process unchanged, and screen the dosage of prescription excipients.

[0086] 8.3.1 Prescription and preparation process The prescription design (specification: 50 mg / ml, batch: 50 vials) is shown in Table 5 below:

[0087] Table 5

[0088]

[0089] The preparation process of Comparative Examples 7 to 14 is the same as that of Example 5.

[0090] 8.3.2 The pH value and particle size test results are shown in Table 6 below

[0091] Table 6 Test results

[0092]

[0093]

[0094] 8.3.3 Experimental Conclusion

[0095] From the above test results, the change of sodium citrate and sodium chloride dosage has little effect on particle size; poloxamer has little effect on particle size when it is 1.7%, 2.5% and 3%. When poloxamer is not added, it is found that the particle size after homogenization is micron-level and not dispersed. Sodium citrate is between 0.24% and 0.36%, and the optimal value is 0.3%; sodium chloride is between 0.8% and 1.0%, and the optimal value is 0.9%; poloxamer is between 1.7% and 3.0%, and the optimal value is 2.0%.

[0096] 8.4 Stability Study

[0097] 8.4.1 Stability test: The test sample (using Example 5) was subjected to high temperature light irradiation, accelerated test, and long-term test.

[0098] (1) High temperature light: Place the test sample in a suitable static container with the opening opened, and place it at 60℃ for 10 days. Take samples on the 10th, 10th and 30th days, and test the key stability items of the sample (pH value, content, particle size, Zeta potential). If the test sample's indicators are lower than the specified limits, perform the same method at 40℃. If there is no obvious change at 60℃, do not perform the 40℃ test.

[0099] (2) Accelerated test: The test sample is packaged as sold in the market. It is placed at 40℃±2℃ for 6 months. The equipment used should be able to control the temperature ±2℃, relative humidity ±5%, and monitor the actual temperature and humidity. Samples are taken at the end of the first month, second month, third month, and sixth month of the test, and the samples are tested according to the key stability inspection items.

[0100] (3) Long-term test: 3 batches of test products, commercially available packaging, placed at 25°C ± 2°C and 65% ± 5% relative humidity. Sampling points: 3 months and 6 months.

[0101] Table 7

[0102]

[0103] 8.4.2 The test results of pH value, particle size and Zeta potential are shown in Table 8 below:

[0104] Table 8

[0105]

[0106]

[0107] 8.4.3 Experimental conclusion:

[0108] From the above test results, the pH value did not change much before and after sterilization. After 10 days of exposure to light and high temperature, the pH increased by about 0.4, but after 30 days, the pH value increased significantly, approaching the limit (6-8). The reason was later found to be the compatibility of the rubber stopper. To ensure the stability of the results, 3 homogenization times were selected. The particle size before and after sterilization differed by about 20nm. There was almost no increase under light and high temperature conditions, and the results were all less than 200nm. The absolute values ​​of the Zeta potential before and after sterilization were both greater than 30mV.

[0109] Although the present invention has been disclosed as above in terms of preferred embodiments, it is not intended to limit the present invention. Anyone familiar with the technology may make various changes and modifications without departing from the spirit and scope of the present invention, all of which are within the scope of protection of the present invention.

Claims

1. A nano carbon suspension injection, characterized in that: Each 1000mL of nano-carbon suspension injection includes: 20-100g of nano-carbon, 17-30g of poloxamer as a suspending agent, 2-4g of sodium citrate as a pH regulator, 8-10g of sodium chloride, and the remainder is water for injection; the nano-carbon is carbon black; The nanocarbon suspension injection is steam sterilized at 115-130° C. for 10-30 min, and the particle size after sterilization is 100 nm-220 nm; The nano-carbon is obtained by pretreatment, which includes: degreasing the nano-carbon with ethyl acetate, washing it with acid, washing it with water until it is nearly neutral, washing it with alkali, and then washing it with water until it is nearly neutral to obtain the nano-carbon.

2. A method for preparing the nanocarbon suspension injection according to claim 1, characterized in that: The following steps are involved: S1 Pretreatment of nanocarbon: After the nanocarbon is degreased with ethyl acetate, it is first washed with acid, then washed with water until the nanocarbon is nearly neutral, then washed with alkali, and finally washed with water until the nanocarbon is nearly neutral, thus obtaining; S2: Weigh each raw material and auxiliary material according to the above formula, then take 90% v / v of the above formula amount of water for injection, add the weighed sodium chloride and stir until it is completely dissolved to obtain a saline solution; S3: adding the weighed sodium citrate and poloxamer to the saline solution obtained in S2 and stirring until they are completely dissolved to obtain an auxiliary material solution; S4: adding the weighed nano-carbon to the auxiliary material liquid obtained in S3 and stirring evenly, and then adding the remaining amount of injection water to make up the volume to obtain a fixed volume solution; S5: homogenize the fixed volume solution obtained in S4 at a rotation speed of 15000-20000 rpm for 3-10 min, and then homogenize at a pressure of 15000-30000 psi for 1-5 times, and then fill and cap, and then steam sterilize at 115-130°C for 10-30 min.

3. The method for preparing the nano-carbon suspension injection according to claim 2, characterized in that: The mass of nanocarbon in step S1: the volume of ethyl acetate is 1 g: 5-12 ml.

4. The method for preparing the nano-carbon suspension injection according to claim 2, characterized in that: The acid described in step S1 is HNO3; the mass of the nanocarbon described in step S1: the volume of the acid is 1g: 3-5ml.

5. The method for preparing the nano-carbon suspension injection according to claim 2, characterized in that: The base described in step S1 is NaOH; the mass of the nanocarbon described in step S1: the volume of the base is 1g: 3-5ml.

Citation Information

Patent Citations

  • Method for preparing nano carbon mixed suspension composition

    CN1181134C

  • Nano carbon suspension injection

    CN1935263A

  • New uses of nanometer charcoal suspension injection

    CN104971365A

  • Nano carbon mixed suspension composition and its preparing method

    CN1458185A